FRI0181 Effectiveness of biological therapy using a treat to target strategy in patients with rheumatoid arthritis. (23rd January 2014) - Santos-Moreno, P.; Sandoval, C.; Villarreal, L.; Real, A. P.; Boon, P.; Palomino, A.; Urbina, A.; Bello, J.
Abstract : Background: The importance of early effective therapy, implications of disease activity in progression and use of composite disease activity measures in rheumatoid arthritis (RA), led to developing of defined therapeutic targets and tools to achieve them resulting in the Treat to Target (T2T) initiative. This strategy is being used last 2 years in Colombia in a specialized in RA center. Objectives: The aim of this study was to describe general change in Disease Activity Score 28 (DAS28) using A T2T strategy during a 24 month period in RA patients treated with biological DMARDs. Methods: A descriptive cross-sectional study was performed. Patients from a rheumatologic center with diagnosis of RA (ACR 1987 and 2010 ACR/EULAR criteria) were assessed applying a T2T strategy. A standardized follow-up was designed using DAS28: every 3-5 weeks (DAS28 > 5.1), every 7-9 weeks (DAS28 ≥ 3.2 and ≤ 5.1), and every 11-13 weeks (DAS28 < 3.2). It was measured tender joint counts, swollen joint counts, DAS28 and HAQ at every visit. In case of DAS28 > 3.2 it was mandatory to introduce adjustments in treatment based on a predetermined clinical guideline. Were included patients who seen at least 6 times their doctor. We calculated percentages and averages from this data and divided patients in two groups: remission-low disease activity (Rem/LDA) patients and moderate-severe disease activity (MDA/SDA) patients. Global change in DAS28, joint counts and HAQ was determined at beginning, 6, 12, 18 and 24 months an assessed using Chi-square test. Results: 357 patients were included in this study, 314 (87.9%) women and 43 (12.1%) men. All patients had established disease (more than 2 years of duration) and average age 56.4 y/o. Regarding entire cohort, majority of patients (80.8%) were using anti-TNFs, mainly infliximab (49.5%) and adalimumab (20.2%). At initial visit, we found only 43% of patients in Rem-LDA activity and 57% patients in MDA/SDA activity according to DAS28. At 6, 12, 18 and 24 months of follow-up we found improvement to 51%, 62%, 62% and 75% respectively in patients of Rem/LDA group. On the other hand was observed a decrease on proportions of patients in MDA/SDA group. The difference of medians for each variable showed improvement with statistical significance (p < 0.00). It was not established improvement in HAQ. Conclusions: This study shows general improvement of DAS28 in RA patients treated with biological DMARDs and applying a T2T strategy; it was found a globally increase in the percentage of patients in Rem-LDA activity group and decrease in MDA/SDA group. Standard T2T follow-up in patients with RA should be done based on: correct use of disease activity scores and visits/treatment decisions based on, and was verified that achieving remission/LDA is a realistic goal in clinical practice. But, after 2 years there is a patient's fourth refractory to treatment with biologicals. Disclosure of Interest: None Declared